Pengaruh 3C Marketing 4.0 Terhadap Revisit Dimediasi Consumer Journey serta Dimoderasi Conversation: Studi Kasus pada Konsumen Shopee di Wilayah Kabupaten Bekasi - Surya Bintarti; Nadine Arofafi Atus Safina (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Customer perception of experience quality, including direct interaction and environmental quality, is crucial. A positive consumer journey is vital for understanding consumer desires during shopping, influenced by communal activation, co-creation, and currency. There is research to suggest that consumer experience may not have a significant impact on revisit, suggesting other variables affect consumer journeys and revisits. This study examines Conversation's role in influencing consumer journeys and revisits. Data from 102 respondents were collected and tested, demonstrating the feasibility of analysis using SmartPLS 0.3 and 0.4. The respondent selection technique that uses non-probability sampling tends to use purposive sampling. This study concludes the following 1) The roles of communal activation, co-creation, and currency have not been able to help create a consumer journey for Shopee customers. 2) The mediating role of the consumer journey for communal activation, co-creation, and currency has not been able to make consumers revisit. 3) The role of conversation as a mediator for communal activation, co-creation, and currency on revisit with the mediation of the consumer journey has not been able to support revisits by Shopee customers.